Carpal arch space increased by volar force applied to the skin surface above the carpal tunnel. (February 2023) - Zhang, Hui; Jordan, David; Li, Zong-Ming
Abstract: Background: Carpal arch space augmentation can help decompress the median nerve. The augmentation can be achieved by mechanical manipulations utilizing the biomechanics of the tunnel structure. The purpose of this study was to expand the carpal arch in vitro by applying volar forces on the surface of the wrist. Methods: The mechanism was implemented in eight cadaver hands by attaching a volar force transmitter to the palmar surface of the wrist and pulling the transmitter volarly at six force levels (0, 3, 6, 9, 12, and 15 N). Ultrasound images of the cross section at the distal carpal tunnel were collected for morphological analysis. Findings: The carpal arch height, width, and area were significantly altered by the volarly applied force ( P  < 0.001). The arch height and area were increased but the arch width was decreased by the force. Pearson's correlation coefficient showed that there was a positive correlation between the arch height and force magnitude; and between the arch area and force magnitude. A negative correlation existed between the arch width and force magnitude ( P  < 0.001). The magnitude of change of the arch height, width, and area was increased as the force magnitude increased. Interpretation: This study demonstrated that applying external forces on the wrist skin to increase the carpal arch space was feasible. The magnitude of the force influenced its effect on altering the carpal arch. Study limitations include small sample size and inclusion of male specimens. Future in vivo work is needed for clinical translation feasibility. Highlights: External volarly-directed forces were applied to the volar wrists of cadaveric specimens. The volarly-directed forces led to increases in the carpal arch height and area. This method has the potential for in vivo application to relieve carpal tunnel syndrome.